Impact of household cleaning products on indoor air quality and respiratory health - Iriarte, Josselyn J.; Álvarez, Ariana L.; Rodríguez, Yaniset (Revista Gregoriana de Ciencias de la Salud, 2025)
Using chemicals in the home improves the quality of life but also poses significant risks to health and the environment, especially in closed spaces. This study analyzed the impact of cleaning products on indoor air quality and respiratory health in Ecuador, where surveillance and awareness of this problem are limited. Through a qualitative narrative review, information from recent scientific and regulatory bases was collected from a total of 45 bibliographic sources, identifying that some of the chemical components of cleaning products can affect respiratory and neurological health, especially in children and older adults, aggravated by the structures and location of the homes. The results highlight the need for strict regulations and educational strategies that promote the safe use of these products. More research into its local impact and the development of sustainable solutions is recommended.